Which lymph node dissection template is optimal for radical cystectomy? A systematic review and Bayesian network meta-analysis - Qi, Wenqiang; Zhong, Minglei; Jiang, Ning; Zhou, Yongheng; Lv, Guangda; Li, Rongyang; Shi, Benkang; Chen, Shouzhen (Frontiers in Oncology, 2022)
Objective This study aims to determine the optimal pelvic lymph node dissection (PLND) template for radical cystectomy (RC). Methods A systematic search was conducted using the PubMed, Embase and Cochrane Library database in December 2021. Articles comparing recurrence-free survival (RFS), disease-specific survival (DSS), overall survival (OS), and postoperative complications among patients undergoing limited PLND (lPLND), standard PLND (sPLND), extended PLND (ePLND), or super-extended PLND (sePLND) were included. A Bayesian approach was used for network meta-analysis. Results We included 18 studies in this systematic review, and 17 studies met our criteria for network meta-analysis. We performed meta-analyses and network meta-analyses to investigate the associations between four PLND templates and the RFS, DSS, OS, or postoperative complications. We found that the ePLND group and the sePLND group were associated with better RFS than the sPLND group (Hazard Ratio [HR]: 0.65, 95% Credible Interval [CrI]: 0.56 to 0.78) (HR: 0.67, 95% CrI: 0.56 to 0.83) and the lPLND group (HR: 0.67, 95% CrI: 0.50 to 0.91) (HR: 0.70, 95% CrI: 0.49 to 0.99). For RFS, Analysis of the treatment ranking revealed that ePLND had the highest probabilities to be the best template. There was no significant difference between the four templates in DSS, however, analysis of the treatment ranking indicated that sePLND had the highest probabilities to be the best template. And We found that the sePLND group and the ePLND group were associated with better OS than lPLND (HR: 0.58, 95% CrI: 0.36 to 0.95) (HR: 0.63, 95% CrI: 0.41 to 0.94). For OS, analysis of the treatment ranking revealed that sePLND had the highest probabilities to be the best template. The results of meta-analyses and network meta-analyses showed that postoperative complications rates did not differ significantly between any two templates. Conclusion Patients undergoing sePLND and ePLND had better RFS but not better DSS or OS than those undergoing lPLND or sPLND templates, however, RFS did not differ between patients undergoing sePLND or ePLND. Considering that sePLND involves longer operation time, higher risk, and greater degree of difficulty than ePLND, and performing sePLND may not result in better prognosis, so it seems that there is no need for seLPND. We think that ePLND might be the optimal PLND template for RC. Systematic Review Registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022318475.